Det er en tysker eller: Alt det her med tysk teater - Albinus, Jens (Peripeti, 2022)
It is a German – or: All this about German theatre The essay focuses on actor Jens Albinus’ relationship with German theatre from a very early age and later during his professional career in Germany working with directors such as Frank Castorf and Stefan Bachmann. The essay portrays the rise and fall of Volksbühne as an epicenter of vital European theatre in the nineties. Albinus also reflects on aspirations of a similar approach at The Royal Theatre after the Millennium and on the importance of dramaturgical knowledge and vocabulary for actors.